2016
DOI: 10.3758/s13414-016-1257-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a no-go Task 2 on Task 1 performance in dual - tasking: From benefits to costs

Abstract: When two tasks are combined in a dual-task experiment, characteristics of Task 2 can influence Task 1 performance, a phenomenon termed the backward crosstalk effect (BCE). Besides instances depending on the (spatial) compatibility of both responses, a particularly interesting example was introduced by Miller (2006): If Task 2 was a no-go task (i.e., one not requiring any action at all), responses were slowed in Task 1. Subsequent work, however, also reported the opposite result-that is, faster Task 1 responses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 28 publications
(75 reference statements)
2
23
0
Order By: Relevance
“…First, RT2s for frequent responses were shorter than those for less frequent responses, supporting the idea that participants indeed prepared for the more likely response alternative. Second, in neutral blocks, RT1 was shorter when Task 2 was a no-go trial, replicating results reported by Janczyk and Huestegge (2017). Most important, this pattern was reversed in biased blocks, thus the no-go BCE reemerged when preparation of a Task 2 response was encouraged.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…First, RT2s for frequent responses were shorter than those for less frequent responses, supporting the idea that participants indeed prepared for the more likely response alternative. Second, in neutral blocks, RT1 was shorter when Task 2 was a no-go trial, replicating results reported by Janczyk and Huestegge (2017). Most important, this pattern was reversed in biased blocks, thus the no-go BCE reemerged when preparation of a Task 2 response was encouraged.…”
Section: Discussionsupporting
confidence: 79%
“…Motivated by the different suggestions advanced in the previous literature Janczyk & Huestegge, 2017;Miller, 2006;Röttger & Haider, 2017), the present study provides a direct test that preparation of a Task 2 response and its inhibition in no-go trials is the reason for performance decrements in Task 1, when Task 2 is a no-go task-a phenomenon known as the no-go BCE. More generally, the present results support the view that reduced preparation for Task 2 can reduce performance decrements in Task 1.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Closer relatives to our own design are dual-task studies (with two distinct stimuli for each task) involving a go/nogo task as Task 2. For example, Miller (2006) showed that trials involving a no-go stimulus (vs. a go stimulus) in Task 2 were characterized by a Task 1 RT increase (see also Janczyk & Huestegge, 2017;Miller & Durst, 2014, 2015. It was assumed that this effect is based on an inhibitory response triggered by the no-go stimulus, which (either directly or via its transformation into a dedicated Binhibitory response^selection process) eventually prolongs Task 1 processing (see Röttger & Haider, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Miller (2006), for example, used a go/no-go task for Task 2. When Task 2 was a no-go trial, RT1s were longer compared to when Task 2 required a go trial, which is often referred to as the no-go BCE (see also Janczyk & Huestegge, 2017;Ko & Miller, 2014;Röttger & Haider, 2017). Although similar to the compatibility-based BCE at a phenomenological level, recent evidence by Janczyk (2018, 2019) suggests that the no-go BCE arises due to Task 2 response selection influencing the motor execution of Task 1 (but see Röttger & Haider, 2017, for a different opinion).…”
Section: Limitations Implications and Future Researchmentioning
confidence: 99%